2022
DOI: 10.20479/bursauludagziraat.1151248
|View full text |Cite
|
Sign up to set email alerts
|

Determination Of Germination And Some Early Growth Parameters Of Cress (Lepidium sativum L.) Seeds Under Different Lead Concentration Stress And Vermicompost Pretreatments

Abstract: Bu çalışma, Bu-Ter tere (Lepidium sativum L.) tohumlarına ön uygulama olarak ağır metal kurşunun farklı konsantrasyonları ve vermikompost uygulamasının çimlenme ve fide gelişim parametrelerine etkisi belirlenmesi amacıyla tesadüf parselleri deneme desenine göre üç tekrarlamalı olarak yürütülmüştür. Çalışma Siirt Üniversitesi Bahçe Bitkileri Bölümü Laboratuvarında gerçekleştirilmiştir. Denemede kullanılan uygulamalar 0, 500, 1000, 1500 ppm, vermikompost, 500 ppm+vermikompost, 1000 ppm+vermikompost, 1500 ppm+ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Bayraktar and Boz (2020) revealed with their study that 70.5% of farmers know the effects of pesticide overuse on environment and 29,5% of them does not have any knowledge about that issue. Erbek et al (2018), found as the result of their research that 63.7% of farmers think that pesticides destroy environment. Table 12 indicates the views of farmers about damages of pesticide overuse on environment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Bayraktar and Boz (2020) revealed with their study that 70.5% of farmers know the effects of pesticide overuse on environment and 29,5% of them does not have any knowledge about that issue. Erbek et al (2018), found as the result of their research that 63.7% of farmers think that pesticides destroy environment. Table 12 indicates the views of farmers about damages of pesticide overuse on environment.…”
Section: Resultsmentioning
confidence: 99%
“…Rate of farmers who deliver pesticides and fertilizers from cooperatives is relatively low (5.8%). According to another study, 75.1% of farmers deliver pesticides from pesticide dealers (Erbek et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations